One-loop divergences in the 6D , N=(1,0) abelian gauge theory; Physics Letters B; Vol. 763 - Bukhbinder I. L. Iosif Lvovich; Ivanov E. A. Evgeny Aleksandrovich; Merzlikin B. S. Boris Sergeevich; Stepanjyants K. V. Konstantin Viktorovich (2016, 2016)
Title screen